Exercise-induced arousal affects free-choices to inhibit. (March 2018) - Dall'Acqua, Tommaso; Li, Chunting; Ceccarini, Francesco; Grigoletto, Davide; Marcolin, Giuseppe; Paoli, Antonio; Castiello, Umberto
Abstract: Objectives: Previous research has demonstrated that exercise–induced arousal has the ability to improve the stopping of an already initiated response. So far the effects of arousal on response inhibition have been investigated with paradigms concerned with inhibition driven by external stimuli. Since in everyday life situations the origin of decisions to inhibit might be entirely internally driven, the present study aims to explore whether intentional action and inhibition responses depend on the physical exertion in a cycle ergometer test. Design and method: While cycling in conditions of low and high exercise-induced arousal, participants were asked to respond to cued and free-choice targets following the presentation of three varieties of masked primes that could elicit congruent or incongruent prime-response conflicts. Results: In condition of high exercise-induced arousal an improvement on reaction times was observed in both cued and free-choice action conditions and less omission errors in cued action trials. Concerning free-choice behavior, overall participants made more 'action' choices when compared to the low arousal condition. Conclusions: Our results widen previous evidence by showing that as for externally driven cognitive processes, also intentional action and inhibition choices are modulated by exercise. Under specific conditions arousal helps individuals to perform the tasks rapidly and efficiently even when task' requirements are entirely internally driven. However higher-order processes, such as making a free-choice, resulted impaired. Highlights: Masked primes modulated reaction times in both high and low arousal conditions. Masked primes increased the proportion of free-choices to act and to inhibit. Exercise-induced arousal speeded up reaction times of free and cued responses. Exercise-induced arousal increased free-choices to act overall. Stimulus-driven inhibition and intentional inhibition might rely on partially distinct cognitive mechanism.